Optimal digestible protein level for bullfrog tadpoles - Pinto, Donovan Filipe Henrique [UNESP]; Mansano, Cleber Fernando Menegasso [UNESP]; De Stéfani, Marta Verardino [UNESP]; Pereira, Marcelo Maia (Elsevier B.V., 2015)
In view of the importance of tadpole rearing to obtain good results of frog farming, the objective of this study was to determine the optimal digestible protein (DP) level for bullfrog tadpoles. Tadpoles were fed isoenergetic diets (15.4 kJ DE g(-1)) containing 21, 23, 25, 27, 29 and 31% DP. The following parameters were evaluated: weight gain, feed intake, dietary protein intake, feed conversion, specific growth rate, protein efficiency ratio, and deposition of protein, fat, water and ashes. The optimal level of DP for weight gain estimated by broken-line regression analysis was 27.7%. Feed intake decreased and protein intake, specific growth rate and feed conversion increased with increasing levels of DP in the diet. No significant difference was observed for protein efficiency ratio. Tadpoles fed diets containing 27, 29 and 31% DP exhibited higher deposition of protein, water and ashes and lower fat deposition. The results suggest 27.7% DP for bullfrog tadpoles.
Keywords: Body composition; Lithobates catesbeianus; Nutrition; Performance